EFFECT OF IDLE TIME AND BERTHING TIME ON LOADING PRODUCTIVITY IN SURABAYA CONTAINER TERMINAL - Ivanhoe, Ivanhoe; Sumali, Bambang (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Improving loading and unloading efficiency at container terminals is a significant challenge in the maritime industry, with idle time and berthing time at the Container Terminal being key factors influencing loading productivity and potentially causing disruptions in the supply chain and reducing customer service quality. This study aims to determine the effect of idle time and Berthing time on loading and unloading productivity at the pier of the ocean-going container terminal Surabaya (TPS) Pelindo III.